Analisis Penderita Rabun Jauh (Miopi) pada Mahasiswa Biologi Universitas Islam Negeri Sunan Gunung Djati - Awaludin Firdaus; Ateng Supriyatna (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Myopia or can also be called nearsightedness is a disorder in the human eye that is not corrected with cataracts and infectious diseases. The purpose of this study is to determine the factors that can cause biology students class of 2022 UIN Sunan Gunung Djati to be affected by nearsightedness. This research method is quantitative in nature. Data collection was used by purposive sampling with the main data obtained from a questionnaire in the form of a google form distributed to biology students of the Class of 2022 UIN Sunan Gunung Djati. The results of this study showed the distribution of the highest percentage of age, namely in students aged 17-18 years with a percentage of 73.5%, the distribution of the percentage of sex with the highest percent number of 85.3% with the female gender, the distribution of the percentage of using gadgets or laptops 67.6% of 34 respondents using it for more than 8 hours per day, while 32.4% of respondents who used gadgets or laptops less than 8 hours per day. As many as 17.6% of students experience nearsightedness caused by genetic factors and 82.4% of students experience nearsightedness not caused by genetic factors.